EVALUASI PENGGUNAAN AKTIVISME KPOP FANS DALAM MENDUKUNG PILIHAN POLITIK DI PILPRES 2024 - Islamiyah, Hanifah (Bawaslu Provinsi Jawa Barat, 2024)
This article discusses the phenomenon of K-pop politicization on the X social media platform, with a focus on the Anies Bubble case during the 2024 Election in Indonesia. The research uses attribution theory to understand the motivations behind political activism in the K-pop fandom community. The research method used is a case study with qualitative descriptive analysis. Anies Bubble is an anonymous account on X that supports Anies Baswedan with a style and culture similar to K-pop fans. Although anonymous, this account played an important role in political campaigns and fundraising for the AMIN couple. The research highlights a pattern of anonymity in K-pop fandom culture, where fans want to separate their online identities from their real lives. K-pop fandom culture is also noted for its significant financial support of its idols, which often leads to mass consumerism and wastefulness. Fans not only idolize them emotionally, but also buy albums, merchandise, and collect photo cards as a form of financial support. The practice of exchanging